Enhancing empathy among medical students via reflective writing - Muhammad Jawad Hashim; Moien AB Khan; Alexander Kieu; Fatima Mohammed Khalfan Alkaabi; Fakhra Khalifa Abdulla Al Rubaei; Maitha Musabbeh Khamis Alfazari; Meera Ahmed Khalfan Alneyadi; Rouda Hamad Saeed Alsaedi; Romona Govender (Canadian Medical Education Journal, 2024)
Implication Statement